Some issues on the design of a solar vehicle based on hybrid energy system - Spina, Marcelo Alberto (2012)
The conception and assembly of an experimental Hybrid Electric Vehicle based on the combination of human energy contribution and photovoltaic solar energy is presented in this manuscript. The vehicle has a battery for storing the energy provided by both systems. The application’s aim is to achieve the lowest possible energy consumption for the vehicle’s movement, with photovoltaic modules as the main electricity source. The development of the solar vehicle was motivated by a Latin-American solar vehicles race about 1000km across the Atacama Desert in Chile, South America. The main constructive aspects, energy issues and experimental results are presented.